Pengaruh E-Service Quality dan E-Trust Terhadap E-Customer Satisfaction Dalam Meningkatkan E-Customer Loyalty ( Pada Aplikasi Penyedia Layanan Transportasi Online Grabbike di Jakarta Barat ) - Della Anisa Putri; Naili Farida; Sari Listyorini (Universitas Diponegoro, 2024)
Abstract : Transportation services are now very developed with the emergence of online transportation booking services, one of which is the emergence of the Grab application. Grab is a company that utilizes technology to provide transportation booking services only through applications. One of the services provided is delivery by two-wheeled vehicles (GrabBike). Based on the data, Grab experienced a decrease in the index in the top Brand Index data from 2020 to 2023 in the face of its competitors This study was conducted to determine the effect of e-service quality and e-trust on e-customer satisfaction in increasing e-customer loyalty of GrabBike service users in West Jakarta. the type of research is explanatory research. Samples were taken from 100 respondents who had used GrabBike in West Jakarta, using non-probability sampling techniques and purposive sampling approaches. The sample collection technique used a questionnaire which was analyzed using validity test, reliability test, correlation coefficient test, determination coefficient test, two-stage regression test, t test, and path analysis with the help of SPSS For Windows 29.0.2. The results of hypothesis testing show the conclusion that: there is a significant effect of e-service quality on e-customer satisfaction, there is a significant effect of e-service quality on e-customer loyalty, there is a significant effect of e-trust on e-customer satisfaction, there is a significant effect of e-trust on e-customer loyalty, there is a significant effect of e-customer satisfaction on e-customer loyalty, there is an insignificant effect of e-service quality on e-customer loyalty through e-customer satisfaction, there is an insignificant effect of e-trust on e-customer loyalty through e-customer satisfaction. The advice given is that Grab provides service improvements in its application, and pays attention to the risks that can occur in order to increase customer loyalty.Keywords: e-service quality; e-trust; e-customer satisfaction; e-customer loyalty Abstrak : Layanan transportasi kini menjadi sangat berkembang dengan munculnya layanan pemesanan transportasi online, salah satunya kemunculan aplikasi Grab. Grab menjadi perusahaan yang memanfaatkan teknologi untuk menyediakan jasa layanan pemesanan transportasi hanya lewat aplikasi. Salah satu layanan yang diberikan adalah pengantaran dengan kendaraan roda dua (GrabBike). Berdasarkan data, Grab mengalami penurunan indeks pada data top Brand Indeks dari tahun 2020 sampai 2023 dalam menghadapi pesaingnya. Penelitian ini dilakukan guna mengetahui pengaruh e-service quality dan e-trust terhadap e-customer satisfaction dalam meningkatkan e-customer loyalty pengguna layanan GrabBike di Jakarta Barat. tipe penelitian adalah explanatory research. Sampel diambil kepada 100 responden yang pernah menggunakan GrabBike di Jakarta Barat, dengan teknik non probability sampling dan pendekatan purposive sampling. Teknik pengumpulan sampel digunakan kuesioner yang di analisa menggunakan uji validitas, uji reliabilitas, uji koefisien korelasi, uji koefisien determinasi, uji regresi dua tahap, uji t, dan analisa jalur dengan bantuan SPSS For Windows 29.0.2. Hasil pengujian hipotesis menunjukkan kesimpulan bahwa: terdapat pengaruh signifikan e-service quality terhadap e-customer satisfaction, terdapat pengaruh signifikan e-service quality terhadap e-customer loyalty, terdapat pengaruh signifikan e-trust terhadap e-customer satisfaction, terdapat pengaruh signifikan e-trust terhadap e-customer loyalty, terdapat pengaruh signifikan e-customer satisfaction terhadap e-customer loyalty, terdapat pengaruh tidak signifikan e-service quality terhadap e-customer loyalty melalui e-customer satisfaction, terdapat pengaruh tidak signifikan e-trust terhadap e-customer loyalty melalui e-customer satisfaction. Adapun saran yang diberikan adalah Grab memberikan perbaikan layanan dalam aplikasinya, serta memperhatikan risiko-risiko yang dapat terjadi agar mampu meningkatkan loyalitas konsumen.Kata kunci : e-service quality; e-trust; e-customer satisfaction; e-customer loyalty